Variação sazonal das trocas gasosas, turgescência relativa do tronco e produtividade em dois cultivares de seringueira em Votuporanga, SP, Brasil - Conforto, Elenice De Cássia; Cavalcante, Juliane Ribeiro; Pessoa, José Dalton Cruz; Moreno, Rogério Manoel Biagi; Mattoso, Luiz Henrique Capparelli (Sociedade Botânica do Brasil, 2005)
Some reseachers have considered the influence of physiological and agrometerological factors on rubber tree yield, altough the real magnitude of these interrelationships remain unknown. Due to this, a study was carried out with two rubber clones, PB 235 and GT 1, cultivated in Votuporanga,São Paulo State, Brazi, in order to examine the possible correlations between physiological parameters and yield during the dry and wet 2000-2001 seasons. The yield during the period was 4550 kg/ha: PB 235 yield was 59.9%, which was 12.6% higher than GT 1 during the dry season and 29.8 % during the wet season. The photosynthetic rate had varied between 2.19 to 3.46 µmolm-2s-1 in GT 1, and 2.31 to 3.93 µmolm-2s-1 in PB 235; the transpiration rate, between 0.66 to 1.88 mmolm-2s-1 and 0.78 to 1.77 mmolm-2s-1, respectively; and, the stomatal conductance, between 0.021 to 0.041 molm-2s-1 and 0.021 to 0.043 mol m-2s-1, respectively. In both clones, the absence of nocturnal stem turgescence recovery during the dry season could explain the variation of productivity. This was more intense for PB 235 in consequence of the significant decrease of the photosynhtetic rate and carbon assimilation efficiency during this period.

Alguns pesquisadores têm enfocado a influência dos fatores agrometeorológicos e fisiológicos sobre a produtividade da seringueira, mas a magnitude destas relações ainda não é totalmente conhecida. Assim, no presente estudo, investigou-se a possível relação entre alguns parâmetros fisiológicos e a produção de dois cultivares de seringueira, PB 235 e GT 1, cultivados em Votuporanga, Estado de São Paulo, durante o período seco e úmido de 2000-2001. A produção total do período foi de 4.550,5 kg/ha, dos quais PB 235 respondeu por 59,9%, com produção 12,6% maior que a de GT 1 no período seco e 29,8 % no período úmido. Os valores da taxa fotossintética variaram entre 2,19 e 3,46 µmol m-2s-1 para GT 1, e entre 2,31 e 3,93 µmol m-2s-1 para PB 235; a transpiração variou entre 0,66 e 1,88 mmol m-2s-1 e 0,78 e 1,77 mmolm-2s-1, respectivamente; e, a condutância estomática, entre 0,021 e 0,041 molm-2s-1 e 0,021 e 0,043 mol m-2s-1, respectivamente. A ausência de recuperação noturna da turgescência do caule durante o período seco, em ambos os cultivares, poderia justificar a variação da produtividade, que foi mais intensa em PB 235, provavelmente decorrente do significativo decréscimo da taxa fotossintética e da eficiência da carboxilação neste período.
Seasonal variations of gas exchange, relative trunk turgescence and yield in two clones of rubber tree cultivated in Votuporanga, SP, Brazil
Keywords: rubber tree; Hevea brasiliensis; yield; gas exchange; stem turgescence; seringueira; Hevea brasiliensis; produção; trocas gasosas; turgescência do caule